PENDIDIKAN TINGGI DAN PENGANGGURAN TERBUKA: Sebuah Dilema - Siti Sanisah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The current national system of education is claimed not to match the field of work. This phenomenon is the reflection of the high level of unemployment graduated from secondary and tertiary level of education. The issue of unemployment seems to be a conti-nuous debate since the graduates wish to be government employees or labours and staff members of companies, without any willing to be entrepreneurs. A survey on the 2009 workforce nationally showed that 64% and 74% of the secondary and tertiary school alumni, respectively, work in government offices private companies. This indicates that the alumni tend to be unemployed simply because they wait the chance to be officers and labours, and reluctant to run their own business.